w+7=2(w-6)

Simple and best practice solution for w+7=2(w-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for w+7=2(w-6) equation:



w+7=2(w-6)
We move all terms to the left:
w+7-(2(w-6))=0
We calculate terms in parentheses: -(2(w-6)), so:
2(w-6)
We multiply parentheses
2w-12
Back to the equation:
-(2w-12)
We get rid of parentheses
w-2w+12+7=0
We add all the numbers together, and all the variables
-1w+19=0
We move all terms containing w to the left, all other terms to the right
-w=-19
w=-19/-1
w=+19

See similar equations:

| h-31=42 | | 10k+5=-5k-40 | | (x/5)–9=–4+6 | | 2+6=2(w-6) | | −4(−4−b)=13(b+26) | | b*15=120 | | g-45=-6 | | -11(14x+15)=100 | | f-9=11 | | 14.59-2y=9.59 | | 7x−1=5x–7= | | 0.3x+4=28 | | 12.13=c+2.48 | | -6=-1/2a+-14 | | -18=b+17 | | 18=-2m-16 | | 8÷x=10 | | 24^2-10^2=x | | 13-0.25x=18 | | -3(-x+1)=7-2x | | 625=5x^(3/2) | | 2d^2–13d–7=0 | | k*6.4=8.7 | | 33/y=3 | | y+11=-1 | | 50+40x=250+10x | | 5(x+3)-x=19 | | g*13=52 | | 8=14+3x | | 10=2(x-8) | | 12b=5b+28 | | -5x+90=-77 |

Equations solver categories